Implications of ground based and satellite derived measurements on techno-economic evaluation of photovoltaic grid connected system in kajang, malaysia - Balasubramanian B.; Ariffin A.M.; Mei K.T. (Publishing House of the Romanian Academy, 2023)
This research work specifically deals with the examination of utilizing the solar irradiance data from different sources such as land based, National Aeronautics and Space Administration/Surface meteorology and Solar Energy (NASA/SSE), renewable energy technologies screen (RetScreen) simulation software, hybrid optimization model for electric renewables (HOMER), in assessing the financial practicability and feasibility of solar photovoltaic grid connected system (PVGCS) situated at Kajang, Malaysia. The financial implications of using free solar radiation databases which is available to the public versus accurate ground measured data in designing the solar photovoltaic grid connected system had been investigated. Financial studies mainly focused on the different key economic criterions such as net present value (NPV), payback period (PBP) and discounted payback period (DPP). Investigations conducted in Kajang had revealed that satellite based software tools over-predicts the daily average solar irradiation, which in turn provides inaccurate information to the investors and so leads to possibility of financial losses. 2021, Publishing House of the Romanian Academy. All rights reserved.